MULTIPEL SKLEROSIS PROGRESIF SEKUNDER GEJALA KLINIS DIAGNOSIS DAN TATA LAKSANA - Nadia Devianca,* Kartika Maharani,* Darma Imran,* Riwanti Estiasari* (Neurona Majalah Kedokteran Neuro Sains, 2020)
SCLEROSIS MS IS A CHRONIC INFLAMMATORY AUTOIMMUNE DISORDER OF THE CENTRAL NERVOUS SYSTEM CNS AFFECTING THE MYELIN MS IS VERY DETRIMENTAL WHICH CAUSES DISABILITY AND WILL REDUCE THE PRODUCTIVITY AND QUALITY OF LIFE OF THE PATIENTS ESPECIALLY IF IT PROGRESSED TO SECONDARY PROGRESSIVE MULTIPLE SCLEROSIS SPMS WHICH THERE WILL BE A CONTINUOUS WORSENING OF NEUROLOGICAL DEFICITS EARLY DETECTION OF SYMPTOM PROGRESSION CAN BE DONE TO OVERCOME THE PROBLEMS THAT MAY OCCUR IN SPMS